Damage Analysis of Hydraulic Bucket Cylinder on Excavator Komatsu CP-200 At PT. Wiratako Mitra Mulia - Riski Arianda; Masykur; Herri Darsan; Al Munawir; Joli Supardi (LPPM Politeknik Aceh Selatan, 2022)
PT. Wiratako Mitra Mulia is a company engaged in asphalt construction and road repair. At this time PT. Wiratako Mitra Mulia uses several heavy equipment to facilitate the work process, one of the heavy equipment used by PT. Wiratako Mitra Mulia is an excavator which is used for the process of dredging soil, moving materials and leveling the ground. From this, there are several obstacles or problems that occur in the excavator, such as damage to the bucket hydraulic cylinder, in which the bucket hydraulic cylinder has an oil leak, cylinder piston damage and seal leakage, therefore proper and scheduled maintenance is needed so that the damage that occurs to the hydraulic cylinder of the bucket excavator can be minimized so that the work process can run smoothly and do not experience any problems. Therefore, daily, weekly, monthly and yearly maintenance is required. For daily maintenance carried out every day by checking lubricants and performing services, for weekly maintenance inspections are carried out every 60 working hours. For monthly maintenance it is done every 250 working hours and for annual maintenance it is done every 2500 working hours.